2014
DOI: 10.1111/tid.12224
|View full text |Cite
|
Sign up to set email alerts
|

Relative incidences and outcomes of Clostridium difficile infection following transplantation of unrelated cord blood, unrelated bone marrow, and related peripheral blood in adult patients: a single institute study

Abstract: These data indicate that the incidence and prognosis of CDAD after uCBT are comparable with those after uBMT and rPBSCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…This study represents the largest cohort of UCBT recipients with CDI and demonstrates a 100‐day CDI rate of 10.2% and a 1‐year CDI rate of 13.3%. Two smaller studies have evaluated CDI in this population documenting overall CDI rates ranging from 9% to 25% . These rates appear consistent with the 12.5%‐26.9% range documented in the literature for recipients of allogeneic HSCT (allo‐HSCT) .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This study represents the largest cohort of UCBT recipients with CDI and demonstrates a 100‐day CDI rate of 10.2% and a 1‐year CDI rate of 13.3%. Two smaller studies have evaluated CDI in this population documenting overall CDI rates ranging from 9% to 25% . These rates appear consistent with the 12.5%‐26.9% range documented in the literature for recipients of allogeneic HSCT (allo‐HSCT) .…”
Section: Discussionsupporting
confidence: 80%
“…Historically, infections represent a leading cause of morbidity and mortality in this population. In small series, UCBT recipients appear to have substantial rates of CDI, approaching 25% of UCBT recipients, which may be a reflection of overall immune suppression including delay in T‐cell function, iatrogenic immune suppression caused by chemotherapeutics, therapies to treat and prevent graft‐versus‐host‐disease (GVHD), and hypogammaglobulinemia related to underlying disease and transplantation. Immune dysfunction may contribute to the overall host risk that is likely to include additional factors, such as prolonged healthcare exposure, receipt of broad‐spectrum antibiotics, and receipt of chemotherapeutic agents.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of 17 trials and 1453 patients concluded that antibiotic prophylaxis reduced the incidence of fever and bacteremia, but did not impact all-cause or infection-related mortality 28 . C. difficile (C. Diff) was not a focus of our study, but other investigators have reported similar incidence and recovery from C. Diff infections after UCBT, MRD, or MUD 29 .…”
Section: Discussionmentioning
confidence: 89%
“…Of the 550 patients who underwent HCST during the study period, 6% (35/550 patients) subsequently developed CDI. Within the literature, the incidence of CDI after all HSCT ranges from 3–17% . A higher incidence of CDI is reported among patients who underwent allogeneic HSCT .…”
Section: Discussionmentioning
confidence: 99%
“…Within the literature, the incidence of CDI after all HSCT ranges from 3-17%. 8,[19][20][21][22][23] A higher incidence of CDI is reported among patients who underwent allogeneic HSCT. 19,24,25 In our study, we also found that most patients who underwent HSCT and who developed CDI had undergone an allogeneic HSCT.…”
Section: Discussionmentioning
confidence: 99%